Resignification of spaces: action at Rio dos Porcos with class 1702, Tatiana Chagas Memória School, Jardim Maravilha, Guaratiba/RJ (Revista de Ensino em Artes, Moda e Design, 2024)
This study aims to promote Environmental Education at the Tatiana Chagas memória Municipal School, located in the Jardim Maravilha district, Rio de Janeiro, where class 1702 was involved. It is a transdisciplinar proposal that integrates the disciplines of Arts and Sciences. To analyze the territory, we went on a Walk with the school class to Rio dos Porcos. We implemente actions based on the principles of the “Land Charter”. In the methodology, arts and Design approaches were used, such as “Design Thinking”and “Word Cloud”, aiming to make the Research more playful and interesting. Furthermore, the “Bem Viver” proposals by Alberto Acosta (2016) were incorporated in line with the principles of Professor Paulo Freire in “Pedagogy of autonomy” (1996).
Keywords: art; science; environmental education